Monitoring of non-communicable diseases in Belgium. (13th November 2019) - Devleesschauwer, B; Abboud, L A; Bogaert, P; Cornez, A; Raes, L; Scohy, A; Van der Heyden, J; Renard, F
Abstract: : Non-communicable diseases (NCDs) account for the highest share of deaths and burden of disease in Belgium. Nevertheless, there is currently no national plan to prevent and monitor the health impact of NCDs. Recently, two initiatives have been launched by Sciensano, the Belgian institute for health, providing new opportunities for monitoring NCDs in an integrated and comparable way - i.e., the Belgian Health Status Report (HSR) and the Belgian National Burden of Disease Study (BeBOD). The HSR, launched in February 2019, integrates health status information in a continuously updated website: www.healthybelgium.be . Key indicators, identified through literature and stakeholder consultations, highlight specific needs and warning signals. Currently, the HSR integrates self-reported information on NCD prevalence from the Belgian Health Interview Surveys, with objective information on cancer and diabetes from the Belgian Cancer Registry and health insurance data, respectively. Future versions will include a broadened scope with national best estimates for other NCD groups. The BeBOD study was launched in 2016, aiming to provide a first set of internally consistent burden estimates by 2020. BeBOD will complement the HSR by integrating information on morbidity and mortality of NCDs into a single measure of burden of disease - the Disability-Adjusted Life Year (DALY). DALYs quantify the number of healthy life years lost due to disease, and allow comparing the burden of fatal and non-fatal conditions. Annual updates of the BeBOD study will further provide unprecedented opportunities to monitor the impact of NCDs over time. In addition to the new opportunities provided by the HSR and BeBOD study, NCD monitoring requires continued investment in active data collection and integration of available data sources. In term, these NCD monitoring systems will provide a solid basis for evaluating the impact of NCD control policies. Key messages: There is currently no national plan to prevent and monitor the health impact of non-communicable diseases in Belgium. The Belgian Health Status Report and the Belgian National Burden of Disease Study provide new opportunities for monitoring non-communicable diseases in an integrated and comparable way.